Pendampingan Pembuatan Ecoprint Pada Tas Totebag untuk Warga di Desa Ngemplak Purworejo - Jumasa, Hamid Muhammad Jumasa; Hidayat, Nur; Damayanti, Mulia; Wulandari, Handyka; Mutaqim, Imam Nur (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2024)
Ecoprint batik is a product that utilizes biological resources, namely utilizing natural dyes in the manufacturing process. These natural dyes are obtained from tannins or dyes of leaves, roots or stems that are placed on a piece of cloth. Then the cloth is boiled in a large cauldron. The KKN 22 group of Universitas Muhammadiyah Purworejo scheduled an activity to make ecoprint batik for PKK women in Ngemplak Village, Gebang, Purworejo Regency. This activity was chosen because there are still many plants and trees that grow abundantly, so they can be utilized for making Ecoprint on Tote Bags. This activity was attended by 15 participants. The flow of implementation of this activity begins with situation analysis, Focus Group Discussion, preparation, program implementation and; monitoring and evaluation of activities. After the activities were completed, it was seen that the participants were very enthusiastic in participating in the entire series of activities. This can be seen from the start of the preparation to the practice of making batik using ecoprint. Batik creations made by all participants have been successfully created, producing clear and unfaded colors.